2020
DOI: 10.1016/j.heliyon.2020.e05040
|View full text |Cite
|
Sign up to set email alerts
|

Health information technology and hospital performance the role of health information quality in teaching hospitals

Abstract: The research purposed in this paper is to investigate the impact of the health information technology on hospital performance through the health information quality as mediating variable, as new evidence from the teaching hospitals in the north of Jordan. Research design and methodology approach based on a survey that is conducted to collect the requested data to develop a model connect between the health information technologies, health information quality and hospital performance by using the Structural Equa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 93 publications
0
29
0
1
Order By: Relevance
“…Meanwhile, Downing et al (2017) measure emergency clinic performance by applying considerable information investigation. Hospital performance and health information are influenced by the quality of health information technology (Alolayyan et al, 2020). They fostered another way to portray emergency clinic performance that featured likenesses and contrasts among medical clinics and recognized general examples of medical clinic performance.…”
Section: Resources and Reputationmentioning
confidence: 99%
“…Meanwhile, Downing et al (2017) measure emergency clinic performance by applying considerable information investigation. Hospital performance and health information are influenced by the quality of health information technology (Alolayyan et al, 2020). They fostered another way to portray emergency clinic performance that featured likenesses and contrasts among medical clinics and recognized general examples of medical clinic performance.…”
Section: Resources and Reputationmentioning
confidence: 99%
“…The authors then take this a step further by offering a healthcare architecture evaluation framework that may be used to support long-term strategic decision making; i.e., from within the evolving HIS. Reports on health information technology in recent years have shown a growing interest in health as an instrument of governance [ 34 ]. Health information infrastructures offer accurate knowledge for the implementation of policies and systems [ 35 ], using predictive indicators to forecast health outcomes and enhancing the framework of healthcare [ 34 , 36 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The study theoretically confirmed the dominant role of finance to FM performance, given that we found significant indirect effects for all the three performance dimensions and should motivate hospital management to prioritize FM in hospitals as part of sustainable resource management to improve healthcare outcomes. Alolayyan et al (2020) investigated the impact of Health information technology and health information quality on the performance of Jordanian teaching hospitals. The study showed that there is an intertwined and reciprocal relation between Health Information Technologies (HITs), hospital performance, and health information quality.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some studies also have discussed the factors affecting hospital performance, including Puig‐Junoy (2000); Aletras et al (2007); Kazley and Ozcan (2009); Alonso et al (2015); Chu et al (2015); Gholami, Higón, and Emrouznejad (2015); Ancarani et al (2016); Chowdhury and Zelenyuk (2016); Jola‐Sanchez et al (2016); Gearhart and Michieka (2018); Ho and Huang (2020); Amos, Au‐Yong, and Musa (2021); and Alolayyan et al (2020), or have assessed the effectiveness of service quality on hospital operations, such as O'Neill, Rauner, Heidenberger, and Kraus (2008); Chang et al (2011); Gok and Sezen (2013); Lindlbauer et al (2016); Ferreira and Marques (2019); and Veneklaasa et al (2020).…”
Section: Introductionmentioning
confidence: 99%